What Determines the Quality of Institutions? - Islam, Roumeen (World Bank, Washington, DC, 2013)
In trying to explain institutional quality, different authors have come to conflicting conclusions. In tackling the problem themselves, the authors show three things. First, openness is positively and pretty robustly associated with institutional quality. To minimize selection bias, the authors use data sets with the greatest cross-country coverage, though they also test the significance of the variables for smaller sample sizes. The results confirm that both natural and policy measures of openness are important. Concentration of trade in natural resource exports continues to be associated with poor institutional quality after openness in trade is accounted for. Second, "social" variables, such as income inequality or ethnic diversity, are not associated with institutional quality. The significance of the inequality variable disappears when continent dummy variables are included for Africa and Latin America. Third, features of specific institutions, such as freedom of the press and checks and balances in the political system, are positively associated with overall perceptions of institutional quality. These findings hold strongly across different data sets and samples even after the authors control for the variables commonly used in the literature.